Alkylated PTA platforms for mono- and polynuclear pre-catalysts for the aqueous biphasic hydroformylation of 1-octene - Ramarou, Diteboho Selina (Department of Chemistry, 2019)
A series of mono-, di- and trimeric alkylated PTA ligands were synthesised. These ligands were reacted with the dimeric rhodium precursor, [RhCl(COD)]2, to produce the corresponding mono-, di- and trinuclear Rh(I)-PTA complexes. These complexes were then reacted with carbon monoxide to substitute the COD ligands with CO ligands, yielding the carbonyl analogues of the complexes. The ligands and complexes were fully characterised using various spectroscopic and analytical techniques, which include 1H, 13C and 31P NMR spectroscopy, FTIR spectroscopy, mass spectrometry, and elemental analysis. The ligands were found to have good solubility in water at room temperature, while the complexes showed water solubility at elevated temperatures. All the complexes were evaluated as catalyst precursors in the aqueous biphasic hydroformylation of 1-octene. The hydroformylation reactions showed that the complexes (6 – 18) were all active when used as catalyst precursors in the aqueous biphasic hydroformylation of 1-octene to yield aldehydes (linear and branched) and iso-octenes as side products. All complexes exhibited good chemoselectivity for aldehydes with the COD complexes displaying better chemoselectivity towards aldehydes than the CO complexes. However, the CO complexes exhibited better regioselectivity for linear aldehydes than the COD complexes. The trinuclear complex displayed accelerated catalytic rates than the dinuclear complexes which, in turn, displayed faster rates than the mononuclear complexes. The complexes could be recycled three times with a marked decrease in the conversion of 1-octene after each run for each catalyst precursor. Leaching studies showed a significant loss of the metal catalysts into the organic layer after each catalytic run. Mercury poisoning studies were conducted and confirmed that, under the catalytic conditions, all complexes behaved entirely as homogeneous catalysts when evaluated as catalyst precursors for the aqueous biphasic hydroformylation of 1-octene.